Mediasi Lokal sebagai Model Utama Penyelesaian Kasus Perceraian Masyarakat Muslim Kalisat Pasuruan - Nor Salam (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article analyzes the background of the legal pattern of the community at Kalisat Pasuruan in making local mediation as the main model to resolve divorce cases. This study uses a socio-legal approach with the Legal System Theory initiated by Lawrence Meir Friedman. This article is based on the emergence of the Supreme Court Regulation on Mediation in order to change the image of the Religious Courts from judicial paradigm to dispute resolution paradigm, including in divorce cases. The mediation in the case is imperative and the denial of mediation process in the court results in the cancellation of the decision by law. This study concludes that the alignment of the Kalisat community towards local mediation is much more due to non-legal factors which are categorized into elements of legal culture than to structural elements or legal substances. The legal culture element that is intended for example concerns the understanding of the Kalisat community on the teachings of their religion, their perceptions of the proceedings in the Religious Court in resolving divorce cases, or other factors such as the emotional closeness between them and community leaders who are local mediators.